Digital Marketing, Msme Product Marketing Innovation - Suryanto, Dardi (CV. Inara, 2021)
The use of digital media for business is not only an additional marketing activity, but also an integrated communication mechanism that amplifies the impact of every function in an organization by leveraging the power of human networks through a platform. Digital-based marketing is used to get consumers, build their preferences, promote brands, retain consumers, and increase the number of products sold and ultimately increase profits. Digital Marketing allows buyers to get all information about products and can make buying and selling transactions via the internet. Like sellers, they too can monitor, and cater to the needs and wants of potential buyers without time and geographical restrictions. Digital marketing is a two-way communication that can create awareness and engagement in the community for certain products and brands.